Fatores de risco associados aos eventos adversos em pacientes internados com diagnóstico de sepse em um hospital de Sergipe: um estudo de coorte - Souza, Ana Waleska de Menezes Seixas (2019)
Introduction: The safety of the patient is considered a priority attribute of quality health systems. In this regard, mitigating adverse events is one of the necessary prerequisites to guarantee effectiveness in health care. Objective: To analyse the risk factors associated with adverse events in hospitalized patients with sepsis at one of the hospitals in Sergipe. Method: The study was divided into three stages that involved an epidemiological research design and two technological productions. The first stage was a historical cohort study, with data collected from 367 medical records of adult male and female patients hospitalized in the ER, diagnosed with sepsis, as registered on of surveillance of adverse events forms between February 2016 and July 2017.The variables studied were related to patients and outcomes. The data were charted and analyzed using the R Core Team software, version 3.5.1. The second stage consisted of the construction of an information system for the monitoring of adverse events and the third stage consisted of a risk management system for Sepsis. Results: Prevalence was 17.98%. Was found the Charlson Comorbidity Index (RR 2.02 and CI 1.30-3.13), polypharmacy (RR 0.016 and IC 1, 07 - 16,66), the use of blood products (RR 2.33 and IC 1.45 - 3.74) and the use of invasive devices (RR 2.44 and IC 1.50 - 3.97). There was an association between the length of hospital stay and adverse event (p <0.001). There was a difference between the type of adverse event and the classification of the damage (p <0.001). After the multivariate analysis, the ICC was found to be greater than or equal to 8 (RR 1.82 and CI 1.17 - 2.85) were identified as independent risk factors associated with the prevalence of adverse events and the use of four or more invasive devices (RR 2.28 and IC 1.39 -3.74). SIMEA software ensured the optimization of adverse event monitoring time, and SIMGERS ensured the optimization in risk management for sepsis, as well as in the monitoring of new cases. Conclusion: This study demonstrates relevance of risk factors for the occurrence of adverse events and allows the establishment of strategies that improve the quality of care and patient safety. It is possible to affirm that technologies such as these are promising in assisting health professionals with the identification of risk situations, as well as the amount of information generated and likely to be applied / used in additional studies.